1993
DOI: 10.1063/1.465059
|View full text |Cite
|
Sign up to set email alerts
|

Drainage of thin liquid films between relatively smooth surfaces

Abstract: Using a new surface force apparatus, static and dynamic measurements have been conducted to investigate the squeeze of a liquid from the contact between a relatively smooth sphere and a plane. Simple liquids and polymer melts (polyisoprene) have been studied, with different solid surfaces (mica, cobalt, gold, platinum, and steel). It has been found that an ‘‘immobile’’ layer of fluid is present on each solid surface which does not participate in the hydrodynamic flow of the liquid. The thickness of this film i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
119
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(141 citation statements)
references
References 35 publications
19
119
0
3
Order By: Relevance
“…Oppositely, for a n-hexadecane film on a glass substrate, the dynamics of the surface fluctuations is slowed down, revealing the presence of a few nanometer thick immobile layer close to the solid surface, in agreement with previous findings [2,3]. .…”
supporting
confidence: 79%
See 2 more Smart Citations
“…Oppositely, for a n-hexadecane film on a glass substrate, the dynamics of the surface fluctuations is slowed down, revealing the presence of a few nanometer thick immobile layer close to the solid surface, in agreement with previous findings [2,3]. .…”
supporting
confidence: 79%
“…However, the immobile fluid layers observed in the 80's by several authors for wetting liquids [2,3] remain to be confirmed. Such layers are expected to be only a few nanometers thick, and an even better resolution than in ref.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Be it at the molecular size [55] or on larger scales [17,58,82,125,194], roughness and geometrical features have been observed to influence the behavior at liquid-solid interfaces. Not only does roughness leads to an ambiguity as to the exact location of the surface, but it impacts the dynamics of the nearby fluid, leading experimentally either to an increase [58,82,125,194] or a decrease [17] of friction with roughness.…”
Section: Surface Roughnessmentioning
confidence: 99%
“…The development of the Surface Force Apparatus in the 1970's [79,81,154] (see §3.1) has allowed for more than thirty years of precise probing down to the nanometer scale of both structure and dynamics of many Newtonian liquids against mica [28,57,58,72,77,80,89,90,97,129,130]. Experimental methods have included squeeze and/or shear flow for a variety of polar and non-polar liquids displaying a wide range of wetting conditions and shear rates.…”
Section: Newtonian Liquids: No-slip? Slip?mentioning
confidence: 99%